Research on the Cross-Cultural Adaptation of Ethnic Minority College Students on Campus from an Acculturation Perspective - Gao, Ye (International Journal of Social Sciences and Public Administration, 2024)
With the improvement of China's social economy and education levels, the proportion of ethnic minority college students is continuously increasing. Their cross-cultural adaptation process in university environments is critical, as it pertains to students' personal growth, national unity, and social harmony. This paper, drawing from acculturation theory, analyzes the factors influencing the campus acculturation process of ethnic minority college students and explores strategies to enhance campus integration. The aim is to provide references for improving educational management for ethnic minority college students.